Testicular atrophy: A complication of non-mumps orchitis after scrotal exploration for presumed testicular torsion. (September 2016) - Lian, Bertrand SY; Cheong, Yee Ling; Low, Yee; Nah, Shireen Anne
An acute illness related to the scrotum is a common paediatric surgical emergency. Difficulty in ruling out testicular torsion means that scrotal exploration is often performed for other scrotal pathologies, including orchitis. The clinical course of orchitis is usually benign and long-term sequelae are rare. We describe two adolescent boys, previously vaccinated for mumps, whom had scrotal exploration for presumed testicular torsion. Both were found intraoperatively to have orchitis, and both subsequently developed testicular atrophy, within 2 months post-surgery. These cases demonstrate the rare, but potentially devastating, complication of testicular atrophy that may arise in non-mumps orchitis. The causative pathophysiology may involve some degree of testicular compartment syndrome and subsequent ischaemia. Patients must be made aware of the potential for this outcome and be advised on testicular self-examination after surgery.